Insights into structure, codon usage, repeats, and RNA editing of the complete mitochondrial genome of Perilla frutescens (Lamiaceae) - Ru Wang; Yongjian Luo; Zheng Lan; Daoshou Qiu (Scientific Reports)
Abstract Perilla frutescens (L.) Britton, a member of the Lamiaceae family, stands out as a versatile plant highly valued for its unique aroma and medicinal properties. Additionally, P. frutescens seeds are rich in Îś-linolenic acid, holding substantial economic importance. While the nuclear and chloroplast genomes of P. frutescens have already been documented, the complete mitochondrial genome sequence remains unreported. To this end, the sequencing, annotation, and assembly of the entire Mitochondrial genome of P. frutescens were hereby conducted using a combination of Illumina and PacBio data. The assembled P. frutescens mitochondrial genome spanned 299,551 bp and exhibited a typical circular structure, involving a GC content of 45.23%. Within the genome, a total of 59 unique genes were identified, encompassing 37 protein-coding genes, 20 tRNA genes, and 2 rRNA genes. Additionally, 18 introns were observed in 8 protein-coding genes. Notably, the codons of the P. frutescens mitochondrial genome displayed a notable A/T bias. The analysis also revealed 293 dispersed repeat sequences, 77 simple sequence repeats (SSRs), and 6 tandem repeat sequences. Moreover, RNA editing sites preferentially produced leucine at amino acid editing sites. Furthermore, 70 sequence fragments (12,680 bp) having been transferred from the chloroplast to the mitochondrial genome were identified, accounting for 4.23% of the entire mitochondrial genome. Phylogenetic analysis indicated that among Lamiaceae plants, P. frutescens is most closely related to Salvia miltiorrhiza and Platostoma chinense. Meanwhile, inter-species Ka/Ks results suggested that Ka/Ks $$<1$$ < 1 for 28 PCGs, indicating that these genes were evolving under purifying selection. Overall, this study enriches the mitochondrial genome data for P. frutescens and forges a theoretical foundation for future molecular breeding research.